2016
DOI: 10.3346/jkms.2016.31.8.1273
|View full text |Cite|
|
Sign up to set email alerts
|

Simvastatin Reduces Capsular Fibrosis around Silicone Implants

Abstract: Capsular fibrosis and contracture occurs in most breast reconstruction patients who undergo radiotherapy, and there is no definitive solution for its prevention. Simvastatin was effective at reducing fibrosis in various models. Peri-implant capsular formation is the result of tissue fibrosis development in irradiated breasts. The purpose of this study was to examine the effect of simvastatin on peri-implant fibrosis in rats. Eighteen male Sprague-Dawley rats were allocated to an experimental group (9 rats, 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, the bipolar tendency of epithelium in OSMF progression could impact the results if the study were extended to longer time frames, potentially leading to thinner epidermal layers. Our findings are consistent with previous research by Chung et al, who used capsular thickness as a measure for fibrosis [26]. Figure 1B offers compelling evidence of substantial tissue structure damage under the influence of ANE for 4 weeks when compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the bipolar tendency of epithelium in OSMF progression could impact the results if the study were extended to longer time frames, potentially leading to thinner epidermal layers. Our findings are consistent with previous research by Chung et al, who used capsular thickness as a measure for fibrosis [26]. Figure 1B offers compelling evidence of substantial tissue structure damage under the influence of ANE for 4 weeks when compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…This could be attributed to the antifibrotic effects of the released simvastatin. Earlier reports have shown that simvastatin reduces capsular fibrosis around silicone implants when administered orally, by downregulating the expression of connective tissue growth factor (CTGF) and transforming growth factor (TGF)β 1 genes in rodents [23]. Further, resolution of hematoma could be attributed to the fact that simvastatin facilitates its absorption via phagocytosis by increasing the expression of CD36 (cluster of differentiation 36) [24].…”
Section: Discussionmentioning
confidence: 99%
“…137 In a later study testing higher oral doses of simvastatin in rats (15 mg/kg/d), radiation-induced capsular fibrosis around silicone implants was significantly reduced compared with a control group. 138…”
Section: Miscellaneous Drugsmentioning
confidence: 99%